(untitled) (BEOIBERISTIKA - Časopis za iberijske, latinoameričke i komparativne studije (ISSN: 2560-4163 Online), 2022)
In the theoretical part of this work we deal with some of the basic characteristics of swearing and we present theoretical assumptions that aim to provide an answer to how to observe this phenomenon. In the analytical part we analyze the swear words related to the mother collected from printed and digital dictionaries and collections of swear words. We focus on the lexical-semantic and syntactic plan through a comparative framework. The results of the research indicate that, both in Serbian and Spanish, the word mother (and its variants, when it comes to Serbian) is used in rude swear words, the main effect of which is to insult a person while the side effect is to insult that same person’s mother. Bearing in mind that historically the family has played an important role in social relationships, while family members have demanded respect and esteem from other members of the community, we conclude that swearing associated with a family member represents a serious insult. Likewise, swearing related to the mother reflects verbal violence and represents a serious moral insult, which seeks to connect the sacred or socially important (the mother) with the dirty (scatological acts and excretion), the shameful (sexual acts) and the sinful (incest). Considering that the attitude towards the mother in the patriarchal culture is one of the most sacred relationships, it is not surprising that the swear word related to the mother (as an expression of language as well as culture) has found its place in language use of these two communities.